RushNet: Practical Traffic Prioritization for Saturated Wireless Sensor Networks - Liang, Chieh-Jan Mike; Chen, Kaifei; Priyantha, Bodhi; Liu, Jie; Zhao, Feng (SenSys (Conference on Embedded Networked Sensor Systems), 2014)
Network traffic prioritization is gaining attention in the WSN community, as more and more features are being integrated into sensor networks. Real-world deployment experience suggests that WSN brings new challenges to existing problems, such as resource constraints, low data-rate radios, and diverse application scenarios. We present the RushNet framework that prioritizes two common traffic patterns in multi-hop sensor networks: low-priority (LP) traffic that is large-volume but delay-tolerant, and high-priority (HP) traffic that is sporadic but latency-sensitive. RushNet achieves schedule-free and coordination-free delivery differentiations with the following features. First, RushNet works with most data collection protocols to deliver LP traffic. Second, RushNet leverages transmission power difference and radio capture effect to implement on-demand HP packet delivery with low overhead. Third, RushNet proposes a retrodiction technique to help nodes minimize the overhead of recovering LP packet loss due to concurrent HP traffic. We evaluate RushNet performance with micro-benchmarks and a crowdsourced office comfort monitoring deployment. The deployment results suggest RushNet can achieve a throughput close to network capacity, and deliver 98% of the HP packets with a latency of less than four seconds.